Proceedings of International Seminar on Livestock Production and Veterinary Technology 2016
DOI: 10.14334/proc.intsem.lpvt-2016-p.359-364
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of White Muscovy as Parent Stock for the Production of Broiler Ducks

Abstract: In rural areas, male muscovy was commonly crossed with layer ducks for the production of mule ducks to be sold as broiler ducks. However, their population was very few with various plumage colors, and with very low egg production. Muscovy can be used as the male parent stock in a commercial production of mule ducks, but it was preferable if they have white plumage for better carcass performance and with higher egg production. The aim of the study was to evaluate the characteristics of a muscovy population whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
1
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
1
1
1
1
Order By: Relevance
“…The results showed that drakes and ducks from the Semi-deciduous forest had the broadest breast (41.75cm & 36.49cm), followed by Coastal savanna(41.27cm & 35.66cm) and then the Rain forest(40.53cm & 35.10cm). The sexual dimorphism in the trait is expected and agrees with the previous findings(Hailu et al, 2018;Tamzil et al, 2018;Foluke et al, 2020;Kadurumba et al, 2021;Ewuola et al, 2020;Susanti et al, 2016;Yakubu, 2011), who recorded a broader breast for drakes than ducks. Also, the overall mean values recorded for drakes and ducks in the current work concord withHailu et al (2018), who documented 44.50cm for drakes and 35.70cm for ducks.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…The results showed that drakes and ducks from the Semi-deciduous forest had the broadest breast (41.75cm & 36.49cm), followed by Coastal savanna(41.27cm & 35.66cm) and then the Rain forest(40.53cm & 35.10cm). The sexual dimorphism in the trait is expected and agrees with the previous findings(Hailu et al, 2018;Tamzil et al, 2018;Foluke et al, 2020;Kadurumba et al, 2021;Ewuola et al, 2020;Susanti et al, 2016;Yakubu, 2011), who recorded a broader breast for drakes than ducks. Also, the overall mean values recorded for drakes and ducks in the current work concord withHailu et al (2018), who documented 44.50cm for drakes and 35.70cm for ducks.…”
supporting
confidence: 91%
“…It also finds harmony withTamzil et al (2018), who recorded 40.91cm and 35.92cm for drakes and ducks, respectively. The values recorded for the present study, however, are slightly higher than those recorded byRaji et al (2009), Foluke et al (2020,Kadurumba et al (2021),Susanti et al (2016) andYakubu (2011), who discovered a disparity in breast circumference in terms of sex in a relative occurrence of40.57cm & 31.43cm,…”
contrasting
confidence: 77%
See 1 more Smart Citation
“…Ukuran-ukuran tubuh tersebut dapat digunakan sebagai data kajian morfometrik pada itik Muscovy Sebagai analisis dasar untuk mengetahui perbedaan genetik dan karakteristiknya. (Yakubu, 2011) (Brahmantiyo et al, 2003;Fatmarischa et al, 2017;Hapsari et al, 2014;Oguntunji and Ayorinde, 2015;Raji et al, 2009;Sitanggang et al, 2015;Sukmaya and Yayan, 2010;Susanti et al, 2016;Tamzil et al, 2018a;Veeramani et al, 2014;Yakubu, 2011) Materi yang digunakan dalam penelitian ini adalah itik Muscovy jantan dengan jumlah 200 ekor terdiri atas 100 ekor itik jantan dan 100 ekor itik betina. peralatan yang digunakan dalam penelitian ini adalah perlengkapan tulis, timbangan digital dengan ketelitian 0,05 kg, pita ukur, kamera digital, dan jangka sorong.…”
unclassified